Genetic Mutation Analysis in Patients with Congenital Hypothyroidism (Bangladesh Journal of Nuclear Medicine, 2024)
Purpose: Congenial hypothyroidism (CH) is one of the most common inborn endocrine disorders in Bangladesh. Genetic mutation is one of the major causes of CH, which can lead to an absent, hypoplastic, or ectopic thyroid gland or defects in the hormone synthesis pathway. The purpose of this study is genetic mutation analysis in terms of mutations in different genes in already-diagnosed patients with CH who are attending Bangabandhu Sheikh Mujib Medical University (BSMMU). Materials and Methods: This cross-sectional study was carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) from July 2016 to June 2017. A total of 27 diagnosed patients with CH from 24 unrelated families were included. All laboratory procedures were conducted at the Institute for Developing Science and Health Initiatives (ideSHi). Blood samples were used for DNA extraction. Conventional PCR was done for DNA amplification. Direct sequencing of specific regions of PCR products was done. BLAST was used for mutation analysis, and the data were presented as numbers and percentages. Results: This descriptive, cross-sectional study was conducted to see the most commonly found mutations in the TPO, TSHR, and PAX8 genes in diagnosed cases of congenital hypothyroidism. Out of a total of 27 patients, eight had dysgenesis, and 19 had dyshormonogenesis. A total of four TPO gene mutations, namely, 1117G > T, 1193G > C, 2145 C > T, and 2173A > C, were found to be involved with dyshormonogenesis. Among the four mutations, 1117G > T and 1193G >C were in exon 8, and they resulted in a change in the amino acid at protein positions 373 (Ala>Ser) and 398 (Ser>Thr). Other two mutations, namely, 2145C>T and 2173A>C, were found in exon 12. Substitution mutation 2145C>T did not change the amino acid proline to another amino acid at position 715. The substitution 2173A>C resulted in 725Thr>Pro. In the TSHR gene, all three mutations, namely, 2181G>C, 2161G>C, and 1523C>T, were found in exon 10. These mutations eventually lead to a change in the primary amino acid sequence of TSHR peptides. The amino acid substitutions that occurred in the TSHR protein were: 727Glu>Asp, 721Val>Leu, and 508Leu>Ser, respectively. Exon 3 of the PAX8 gene was analyzed, and no mutation was found. Conclusion: This study aimed to conduct a genetic analysis on CH, a prevalent inborn endocrine disorder in Bangladesh, to better understand its causes and develop future management strategies.Bangladesh J. Nuclear Med. 26(2): 115-118, 2023